Revitalizing TESOL in Indonesian higher education: Addressing challenges and solutions for Gen Z students - Afna, Mauloeddin (Accentia: Journal of English Language and Education, 2024)
This study investigated the challenges and solutions in revitalizing language education in the context of Indonesian higher education, with a specific focus on the English Education Department of Tarbiyah dan Teacher Training Faculty of IAIN Langsa, Kota Langsa, Aceh, Indonesia. The study identified the unique needs and preferences of Gen Z students in their English language education journey. By examining their attitudes, motivations, and learning styles, the study overviewed to shed light on the challenges faced by educators in meeting the language learning needs of the students. Additionally, the study explored the innovative teaching methodologies, instructional technologies, ICT-applied for classroom and learner-centered approaches that effectively engage the students. The findings contribute to the development of strategies and recommendations for revitalizing language education in Indonesian higher education, emphasizing the importance of aligning language education programs with the distinctive needs and expectations of the students. Overall, the research outcomes have implications for language educators, policymakers, and institutions involved in language education, aiming to advance language education practices that promote students' language proficiency and better educational experience in Indonesian higher education settings.